2021
DOI: 10.1021/acs.nanolett.1c00999
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Dissipation in Gallium Nitride-Based Light-Emitting Diodes by Piezo-phototronic Effect

Abstract: As a new generation of light sources, GaN-based light-emitting diodes (LEDs) have wide applications in lighting and display. Heat dissipation in LEDs is a fundamental issue that leads to a decrease in light output, a shortened lifespan, and the risk of catastrophic failure. Here, the temperature spatial distribution of the LEDs is revealed by using high-resolution infrared thermography, and the piezo-phototronic effect is proved to restrain efficaciously the temperature increment for the first time. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Under high injection conditions, though the QE decreases, the radiative recombination efficiency becomes less dependent on temperature because of the dominance of the Auger process [154]. Self-heating and heat dissipation is observed to have a significant impact on the reliability of nitride LEDs [155][156][157]. It has been reported that nitride LEDs may fail under a few hours of high temperature (250-300 • C) stress because of degradation mechanisms, such as emission crowding and series resistance increase [158,159].…”
Section: Temperature Dependence and Reliability Of Nitride Ledsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high injection conditions, though the QE decreases, the radiative recombination efficiency becomes less dependent on temperature because of the dominance of the Auger process [154]. Self-heating and heat dissipation is observed to have a significant impact on the reliability of nitride LEDs [155][156][157]. It has been reported that nitride LEDs may fail under a few hours of high temperature (250-300 • C) stress because of degradation mechanisms, such as emission crowding and series resistance increase [158,159].…”
Section: Temperature Dependence and Reliability Of Nitride Ledsmentioning
confidence: 99%
“…To enhance the reliability of nitride LEDs by improving thermal management, techniques such as the incorporation of heat sinks [162,163], flip-chip packaging [164], liquid cooling [165,166], and thermoelectric cooling [167] have been proposed. Very recently, the piezo-phototronic effect has been demonstrated as an effective means of enhanced heat dissipation in nitride LEDs [157] Thermal management continues to be an active area of research and development for the reliable high-temperature operation of nitride LEDs.…”
Section: Temperature Dependence and Reliability Of Nitride Ledsmentioning
confidence: 99%
“…For a better fundamental understanding of piezo-phototronics in the context of photocatalytic hydrogen generation, Schottky and p-n junction mechanism are discussed profoundly in hybrid photocatalytic system sections of this present review. Adding to this, current-density equations, piezoelectric equations, continuity equations, and electrostatic equations are applied as rudimentary governing equations for describing piezophototronics in various applications such as photodetectors, solar cells, LEDs, pressure imaging, and sensors, 43,48,49 but in the catalytic theme, to date, no such strong theoretical support by means of an equation has been reported.…”
Section: Piezo-phototronicsmentioning
confidence: 99%
“…GaN-based light emitting diodes (LEDs) have been extensively studied, but most of the energy are dissipated in form of heat despite the increasing efficiency of devices, especially the blue light LEDs based on InGaN/GaN. [139,140] The GaN LED devices embedded with graphene oxide are capable of emitting bright light at low temperature and thermal resistance. [141] 2D materials such as graphene oxide alleviates the selfheating problems, making the device performance better than conventional ones.…”
Section: Light Emitting Diodesmentioning
confidence: 99%